The effect of salt precipitation on the petrophysical properties and the adsorption capacity of shale matrix based on the porous structure reconstruction. (15th February 2022) - Zhang, Yizhong; Ju, Bin; Zhang, Maolin; Wang, Chenchen; Zeng, Fanhua; Hu, Rongrong; Yang, Long
Highlights: Effects of salt precipitation on the properties of the shale matrix are studied. The 3D porous structure reconstructions of the shale matrix are conducted. Petrophysical properties are simulated based on the reconstructed pore networks. The methane adsorption capacities at different temperatures are predicted. The method complements laboratory measurements or empirical rock property models. Abstract: The study of salt precipitation and its effect on the reservoir physical properties and hydrocarbon adsorption capacity is important to the development of the shale reservoir with high salinity brine. In this study, a brine evaporation (static salting-out) is conducted on the shale matrix sample extracted from the Eocene Qianjiang inter-salt hypersaline lacustrine shale formation located in the Qianjiang Depression, Jianghan Basin, mid-eastern China, to prompt the salt precipitation to reach the exacerbation stage. The porous structure reconstruction technology is applied to study the effect of salt precipitation on the petrophysical properties of the shale matrix. The 3D pore networks of the shale matrix before and after brine evaporation are reconstructed based on 2D high-resolution nanoscale focused ion beam scanning electron microscopy (FIB-SEM) images. Pore-throat structural analyses and fluid flow simulations are carried out on the reconstructed pore networks to generate the physical and fluid flow properties. The density function theory (DFT) and the adsorption potential theory (APT) are combined to predict the CH4 adsorption isotherms of shale matrix with salt precipitation at different temperatures based on the pore size distribution (PSD) obtained from the reconstructed pore networks. The results show that salt precipitation can cause a 23.0% reduction in the porosity and a 47.0% reduction in the absolute permeability of the shale matrix. Salt precipitation has a stronger effect on larger pores and throats, which will cause the destruction of the reservoir fluid flow channels and a large change in the pore size distribution. The CH4 adsorption isotherms that are predicted based on the pore size distribution by the density function theory and the adsorption potential theory show that salt precipitation could cause a reduction of approximately 20.4% in the adsorption capacity, and the absolute adsorption capacity could be even smaller when the temperature is increased from the lab temperature to higher temperatures.